2007
DOI: 10.1523/jneurosci.4672-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Interneurons Facilitate Mossy Fiber Excitability in the Developing Hippocampus

Abstract: Profound activity-dependent synaptic facilitation at hippocampal mossy fiber synapses is a unique and functionally important property. Although presynaptic ionotropic receptors, such as kainate receptors, contribute partially to the facilitation in the hippocampus, the precise mechanisms of presynaptic regulation by endogenous neurotransmitters remain unclear. In this study, we report that axonal GABA A receptors on mossy fibers are involved in the activity-dependent facilitation during development. In immatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…This increased mossy fiber excitability caused by depolarizing action of GABA gradually decreased with development and eventually disappeared at around postnatal day 30. These results suggested that GABA released from interneurons acted on axonal GABA receptors on mossy fibers and contributed at least partially to the activity-and age-dependent facilitation in the hippocampus (472).…”
Section: H Glutamatergic Mossy Fiber Synapses Have An Early Mixed Gamentioning
confidence: 84%
“…This increased mossy fiber excitability caused by depolarizing action of GABA gradually decreased with development and eventually disappeared at around postnatal day 30. These results suggested that GABA released from interneurons acted on axonal GABA receptors on mossy fibers and contributed at least partially to the activity-and age-dependent facilitation in the hippocampus (472).…”
Section: H Glutamatergic Mossy Fiber Synapses Have An Early Mixed Gamentioning
confidence: 84%
“…Another mechanism of activity-dependent signal amplification has been reported at hippocampal mossy fiber (376). In immature hippocampus, repetitive stimulation of the mossy fiber pathway not only facilitates synaptic transmission but also facilitates the amplitude of the presynaptic volley, the electrophysiological signature of the presynaptic action potential in the axon recorded extracellularly.…”
Section: B Signal Amplification Along the Axonmentioning
confidence: 99%
“…All experiments were performed with neurosphere cultures that were passaged Ͻ15 times. Additionally, cultures were exposed to methanol at 320 md/dl for 5 d. Because the GABA type-A (GABA A ) receptor mediates many of ethanol's actions (Ma et al, 2001;Kalluri and Ticku, 2002;Abe et al, 2004), and functional GABA A receptors are present in fetal VZ neuroepithelial cells (Owens et al, 1999;Maric et al, 2001), we also used the GABA A antagonist picrotoxin (at 100 M) (Nakamura et al, 2007), to block the effects of ethanol in some experiments. In control experiments, neurosphere cultures were exposed to picrotoxin by itself (at 100 M) for 5 d to mimic the duration of ethanol exposure.…”
Section: Neurosphere Cultures and Alcohol Treatmentmentioning
confidence: 99%